KEPUTUSAN KONSUMEN TERHADAP PEMBELIAN TANAMAN HIAS SELAMA PANDEMI DI KECAMATAN KOTABUMI SELATAN - Yuni Elmita Sari; Feby Musti Ariska; Sri Puji Lestari (AgriMalS, 2021)
The purposes of this study were 1.) To find out the types of ornamental plants purchased by consumers in Kotabumi Selatan District. 2.) Knowing what factors influence consumer decisions to buy ornamental plants in Kotabumi Selatan District. The method in this research is a survey method. This research was conducted in Kotabumi Selatan Subdistrict, North Lampung Regency because it is one of the regencies in Lampung Province that has a fairly high impact of Covid-19. The location of the research was done intentionally. Accidental sampling method (accidental sample) is used to determine the sample on consumers who buy ornamental plants. Based on the research results, the types of sri fortune (aglaonema), widow bolong (Monstera adansonii), chrysanthemum, and various taro. based on the order of the most fans is Sri Rejeki (Aglaonema). Factors that influence consumers to buy ornamental plants are cultural factors (X1) of 20.02 percent, social factors (X2) of 20.22 percent, personal factors of (X3) 35.41 percent, and psychological factors of 24.35 percent so that the personal factor (X3) of 35.41 percent is the biggest factor influencing consumers to buy ornamental plants.